Revealing the potential of a huge citizen-science platform to study bird migration. (2nd October 2019) - Schubert, Stephanie Caroline; Manica, Lilian Tonelli; Guaraldo, André De Camargo
ABSTRACT: The currently best-known ornithological citizen-science platform is Cornell's eBird, which provides crucial information for bird migration studies. Considering the solid validity of eBird data, and after a validation process, we comparatively explored the data available in the Brazilian-wide platform WikiAves for bird migration studies. We selected five migratory and four resident species as models, controlling for likely sampling biases derived from efforts by the platform collaborators. If data in WikiAves were adequate for migration studies, we respectively expected, after a between-platform comparison, similar yearlong seasonal and non-seasonal occurrence records of all migratory and resident species. Data analysis supported our expectations: eBird and WikiAves data showed consistent temporal occurrence patterns for all evaluated species. Therefore, we selected another six model-species showing literature inconsistency on their migratory behaviour, demonstrating for the first time the potential of a Brazilian citizen-science database – WikiAves – in unveiling geographically seasonal occurrence patterns of the understudied migratory bird species in Brazil. Our study highlights the general public relevance on reducing knowledge gaps about bird migration in Brazil, revealing a feasible strategy to overcome some current logistic barriers that preclude advances in South American bird migration studies, a currently underexplored research area, especially by Brazilian researchers.